Impact of the COVID-19 pandemic on household financial asset allocation: A China population study - Jia, Hongwen; Fan, Shugang; Xia, Miao (Frontiers in Psychology, 2022)
During the COVID-19 pandemic, the Chinese government implemented a "dynamic zero" epidemic prevention policy to stop the spread of COVID-19 within the country based on the principle of life first, but this policy led to an increase in the likelihood of work stoppages and changes in people's psychological expectations, which in turn influenced their behavioral choices. This study aims to understand the impact of COVID-19 and other major public health emergencies on household financial asset allocation. To do so, we conducted an online survey of 712 people in China to measure household financial asset allocation behavior during three different time periods: pre-pandemic, mid-pandemic, and post-pandemic (future aspirations). At the same time, we analyzed the impact of socio-demographic characteristics on risk attitudes. The results show that household financial asset allocation changes significantly in the pre-pandemic, mid-pandemic and post-pandemic periods, and precautionary savings increase among residents. In addition, gender, education level, occupation, and annual income have a significant impact on risk preferences. In conclusion, the pandemic leads to increased economic and social uncertainty, which affects residents' household financial asset allocation, and psychological expectations of economic development play an important role in household financial asset allocation.